Well-defined cyclopropenone-masked dibenzocyclooctyne functionalized polymers from atom transfer radical polymerization. (1st May 2015) - Sun, Peng; Yan, Guowei; Tang, Qingquan; Chen, Yongming; Zhang, Ke
Abstract: Two functional atom transfer radical polymerization (ATRP) initiators (I-2 andI-3 ) were developed bearing a cyclopropenone-masked dibenzocyclooctyne group. ATRP was then explored on three main kinds of monomers for radical polymerization including acrylates, styrenics, and methacrylates based on these novel initiators. By a standard ATRP protocol, the polymerization behavior demonstrated the living characteristics for all three cases and the corresponding well-defined cyclopropenone-masked dibenzocyclooctyne end or middle functionalized polymers were produced conveniently. Since UV irradiation of the cyclopropenone-masked dibenzocyclooctynes could quantitatively release the dibenzocyclooctynes widely used in strain promoted azide-alkyne cycloaddition bioorthogonal click reaction, these novel ATRP initiators and the resultant well-defined polymers should play an important role in the preparation of topological polymers and bio-synthetic polymer conjugates and many other related fields. Graphical abstract: Highlights: Cyclopropenone-masked dibenzocyclooctyne end functionalized ATRP initiators. ATRP of methacrylates, styrenics, and acrylates. UV-induced SPAAC click chemistry.